Attitudes of Kazakh rural households towards joining and creating cooperatives - Kaliyeva, Samal; Areal, Francisco Jose; Gadanakis, Yiorgos (My University, 2020)
The government of Kazakhstan is currently developing strategies and policies to stimulate milk production at an industrial production level to increase milk processing capacity. We use and expand the reasoned action approach as a framework to study the factors underlying the rural household’s motivation to participate in a governmental programme aimed at increasing rural cooperative production in Kazakhstan to increase milk production using primary data acquired from 181 randomly selected dairy households in the Akmola region of Kazakhstan. We account for the rural household’s psychological factors and socio-demographic characteristics along with the household’s risk attitudes, production structure, level of information about the government support programme and cooperatives, cultural aspects as well as the household’s proximity to the main market. A bivariate probit model is used to jointly estimate the impact of these factors on the rural household’s intention to join and create a cooperative. The results show that rural households which hold positive views towards cooperatives, have a relatively high production capacity, are aware/know of cooperatives, and do not have a dairy business as a source of household income are relatively keen to participate in collective actions. Perceived social norms and household risk attitudes also play a significant role in the rural household’s intention to participate in collective actions. Finally, gender and nationality are found to be positively associated with joining and creating a cooperative, while higher educated rural households are found to be less motivated to participate in the programme. In order to stimulate milk production at an industrial production level through a policy that encourages collective action, we recommend a policy that (a) supports rural households which have the capacity to produce and are in need; (b) is attractive to rural households which consider dairy as a source of income; and (c) is well disseminated and well explained to the targeted rural households.
Keywords: cooperative creation policy; dairy households; reasoned action approach; bivariate probit model; Kazakhstan